Factors associated with noncompliance of sodium restriction in hypertensive and heart failure patients at the National Hospital of Cotonou, Benin - Colette Sylvie Azandjeme; Charles-Jérome Sossa; Murielle E. Hounkponou; Yolaine Ahanhanzo-Glèlè; Basilia Sodabi; Carmelle Mizehoun; Aymeric Darboux; Martin Houenassi (AOSIS, 2020)
Introduction: Nutritional therapy in the treatment of high blood pressure and heart failure is a real challenge in terms of compliance of sodium restriction for success of the treatment. The study aims to assess the level of patient compliance with the sodium restriction by salt consumption, prescribed by care providers and the associated factors. Materials and Methods: Total daily salt intake was estimated in a cross-sectional study of 166 hypertensive and heart failure subjects monitored in the cardiology department of the "Centre Hospitalier Universitaire - Hubert Koutoukou Maga" (CNHU-HKM), using two 24-hour recalls combined with a food frequency questionnaire for salt-providing foods. Results: Out of the study, 83.7% of patients had a daily intake above recommendations. Factors associated with the non-compliance of salt restriction were the lack of knowledge of palliative spices and herbs of salty taste (p=0.009) and the consumption of salty snack foods and salty peanuts (p=0.032). Conclusion: Nutritional education and support activities should be carried out to improve the salt reduction compliance for these patients.